KN-93, an inhibitor of calcium/calmodulin-dependent protein kinase IV, promotes generation and function of Foxp3+ regulatory T cells in MRL/lpr mice. (November 2014) - Koga, Tomohiro; Mizui, Masayuki; Yoshida, Nobuya; Otomo, Kotaro; Lieberman, Linda A.; Crispín, José C.; Tsokos, George C.
Abstract Objective: Foxp3+ regulatory T cells (Treg) are pivotal for the maintenance of peripheral tolerance and prevent development of autoimmune diseases. We have reported that calcium/calmodulin-dependent protein kinase IV (CaMK4) deficient MRL/lpr mice display less disease activity by promoting IL-2 production and increasing the activity of Treg cells. To further define the mechanism of CaMK4 on Treg cells in systemic lupus erythematosus (SLE), we used the Foxp3-GFP reporter mice and treated them with KN-93, an inhibitor of CaMK4. Methods: We generated MRL/lpr Foxp3-GFP mice to record Treg cells; stimulated naïve CD4+ T cells from MRL/lpr Foxp3-GFP mice under Treg polarizing conditions in the absence or presence of KN-93; evaluated the number of GFP positive cells in lymphoid organs and examined skin and kidney pathology at 16 weeks of age. We also examined the infiltration of cells and recruitment of Treg cells in the kidney. Results: We show that culture of MRL/lpr Foxp3-GFP T cells in the presence of KN-93 promotes Treg differentiation in a dose-dependent manner. Treatment of MRL/lpr Foxp3-GFP mice with KN-93 results in a significant induction of Treg cells in the spleen, peripheral lymph nodes and peripheral blood and this is accompanied by decreased skin and kidney damage. Notably, KN-93 clearly diminishes the accumulation of inflammatory cells along with reciprocally increased Treg cells in target organ. Conclusion: Our results indicate that KN-93 treatment enhances the generation of Treg cells in vitro and in vivo highlighting its potential therapeutic use for the treatment of human autoimmune diseases.